The GP’s Dilemmas: A Study of Knowledge Need and Use During Health Care Consultations - Timpka, T.; Arborelius, Elisabeth (Methods of Information in Medicine, 1990)
For use in system development, a method based on both qualitative and quantitative data was employed to study the difficulties – the dilemmas – a general practitioner (GP) faces during daily consultac tions. Video recordings were used for stimulated recall of the consultation. From 46 consultations, 262 dilemmas were identified by the 12 GPs involved. Medical dilemmas were encountered during three out of four consultations. Dilemmas in the communication with the patient occurred during two consultations out of three, while dilemmas in the organizational environment and dilemmas challenging the GP’s personal competence occurred during one consultation out of three, respectively. A phenomenological analysis of the comments showed that few dilemmas were described as problems during “hypothetico-deductive reasoning”. In many cases the GP found it difficult to understand the situation as a whole. Based on these qualitative data, a model of the GP’s management of ill-structured complex dilemmas is discussed and proposed, to be taken into account in the development of decision support systems for outpatient practice.
Keywords: Decision-Making; General Practice; Doctor – Patient Consultation; Video Recordings; Qualitative Analysis; Decision Support